Contemporary German Prints Constructivists - Realists : 33 artists of the Federal Republic of Germany. - Grochowiak, Thomas (Stuttgart : Institut für Auslandbeziehungen, 1980)
Albers, Josef ; Geiger, Rupprecht ; Girke, Raimund ; Uecker, Günther ; da Silva Mavignier, Almir ; Quinte, Lothar ; Damke, Bernd ; Fruhtrunk, Günther ; Pfahler, Georg Karl ; Gaul, Winfred ; Haack, Dieter ; Gräsel, Friedrich ; Lenk, Kaspar Thomas ; Heerich, Erwin ; etc.
Contemporary German Prints Constructivists - Realists : 33 artists of the Federal Republic of Germany, Institut für Auslandbeziehungen, Stuttgart, 1980. Selected by Professor Thomas Grochowiak, Recklinghausen
kunstcatalogus
Keywords: Duitsland